Utilization of Kine Master Media as a Learning Media in the Material of Ability to Read Descriptive Text for Class VII - M. Asholahudin; Yayat Ruhiat; Lukman Nulhakim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The objective of this research is to know about the useful of Kine Master as a tool of teaching especially the material about descriptive text in the class of VII Academic Year 2020/2021 SMP Negeri 6 Cilegon then got 82 respondents. The method of this research is experiment research. The result of the study in this reserach as to the achievement of the student is more effective, the average of the score is 88. The questionaire was given to the students declared that the tool of Kine Master could useful by the students. Based on the result of the research, the tool of Kine Master is suitable to use in the process of teaching learning process. The implication of this research is that Kine Master can then be applied in various lessons.